Intraoperative Real-Time Near-Infrared Image-Guided Surgery to Identify Intracranial Meningiomas via Microscope - Muto, Jun; Mine, Yutaka; Nishiyama, Yuya; Murayama, Kazuhiro; Yamada, Seiji; Kojima, Daijiro; Hayakawa, Motoharu; Adachi, Kazuhide; Hasegawa, Mitsuhiro; Lee, John Y. K.; Hirose, Yuichi (Frontiers in Neuroscience, 2022)
Meningiomas are common pathology in the central nervous system requiring complete surgical resection. However, in cases of recurrence and post-irradiation, accurate identification of tumor remnants and dural tail under bright light remains challenging. We aimed to perform real-time intraoperative visualization of the meningioma and dural tail using delayed window indocyanine green (ICG) technique with microscopy. Fifteen patients with intracranial meningioma were administered 0.5 mg/kg ICG a few hours before observation during the surgery. We used near-infrared (NIR) fluorescence to identify the tumor location. NIR fluorescence could visualize meningiomas in 12 out of 15 cases. Near-infrared visualization during the surgery ranged from 1–4 h after the administration of ICG. The mean signal-to-background ratio (SBR) of the intracranial meningioma in delayed window ICG (DWIG) was 3.3 ± 2.6. The ratio of gadolinium-enhanced T1 tumor signal to brain (T1BR) (2.5±0.9) was significantly correlated with the tumor SBR. (p=0.016) Ktrans, indicating blood brain barrier permeability, was significantly correlated with the tumor SBR (p<0.0001) and T1BR (p=0.013) on dynamic contrast-enhanced magnetic resonance imaging (MRI). DWIG demonstrated a sensitivity of 94%, specificity of 38%, positive predictive value of 76%, and negative predictive value of 75% for meningiomas, respectively. This is the first pilot study in which delayed window ICG fluorescent guided surgery was used to visualize meningioma and dural tail intraoperatively with microscopy. DWIG is comparable to SWIG in the mean SBR. Gadolinium-enhanced T1 tumor signal may predict NIR fluorescence of the intracranial meningioma. The blood-brain barrier permeability as shown by Ktrans on dynamic contrast-enhanced MRI can contribute to Gd enhancement on MRI and to ICG retention and tumor fluorescence by NIR.